2014
DOI: 10.1891/1946-6560.5.3.259
|View full text |Cite
|
Sign up to set email alerts
|

Content and Framing of Male- and Female-Perpetrated Intimate Partner Violence in Print News

Abstract: This article investigates the content and framing of newspaper articles reporting male-and female-perpetrated intimate partner violence (IPV). There were 173 newspaper articles coded for IPV severity, typology, and framing. Print news coverage of female-perpetrated IPV was limited; however, when reported, cases of female-perpetrated IPV were more severe, more likely to be described as perpetrated in self-defense, and less likely to be framed in terms of individual factors. For both male and female perpetrators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
9
1
Order By: Relevance
“…Even in the weak violence condition, participants still rated IPV as serious. Content analyses of news stories have shown that IPV with low levels of violence is not frequently depicted in new stories (e.g., Carlyle, Scarduzio, et al, 2014;Sellers et al, 2014). However, the current study finds that presentations of low-severity violence may still impact the individuals reading news stories.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…Even in the weak violence condition, participants still rated IPV as serious. Content analyses of news stories have shown that IPV with low levels of violence is not frequently depicted in new stories (e.g., Carlyle, Scarduzio, et al, 2014;Sellers et al, 2014). However, the current study finds that presentations of low-severity violence may still impact the individuals reading news stories.…”
Section: Discussioncontrasting
confidence: 67%
“…Importantly, research determined that journalists present the same acts of violence differently for male and female perpetrators. For example, in a recent content analysis of IPV news stories, Sellers et al (2014) found that when the same type of IPV occurred (i.e., homicide) female perpetrators were more often portrayed as acting in self-defense than male perpetrators. Perceptions of IPV also differ when male and female perpetrators use severe violence.…”
Section: Severity Of Violencementioning
confidence: 99%
See 2 more Smart Citations
“…Media coverage of IPV has significantly influenced public perception of the issue (Carlyle, Orr, Savage, & Babin, 2014). Some media coverage of IPV has perpetuated public perceptions that IPV is an individual issue (Savage et al, 2016; Sellers, Desmarais, & Tirotti, 2014). Some researchers explain that the impact of media coverage of IPV reduces individuals’ perceived responsibility on this pervasive issue (Carll, 2003; Carlyle et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%